Analisis Pemanfaatan Kredit Oleh Pelaku Usaha UMKM Di Kota Atambua Kabupaten Belu : Studi Kasus Pelaku Usaha Mikro Yang Mengambil Kredit Pada Bank Bni 46 - Selviana Ena; Fransina W. Ballo; Novi Theresia Kiak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the use of credit by micro business actors in Atambua City who use loan funds from BNI46 Bank, as well as to find out the reasons why business actors take credit from BNI46 Bank. The data used in this research is primary and secondary data, which is then analyzed using qualitative descriptive methods. The data collection techniques used in this research are: interviews, observations and documents. The object of this research is the use of credit by micro and small businesses in Atambua City, located around the center of Atambua city. These utilization interests are divided into two interests, namely for production and consumption purposes. First, for the purposes of fulfilling and expanding business capital for trading, a means to make business activities smoother and business performance better than before, expanding business and work opportunities. Second, for consumption needs, which includes personal consumption needs such as paying children's school fees, house rental costs, as well as house maintenance costs and daily living costs.